EPIC-Germany - A Source for Studies into Diet and Risk of Chronic Diseases - Böing, Heiner; Wahrendorf, Jürgen; Becker, Nikolaus (Annals of nutrition & metabolism, 1999)
The ‘European Investigation into Cancer and Nutrition (EPIC)’ represents one of the main scientific activities of the EU program ‘Europe against Cancer’ and is a large-scale cohort study on diet and chronic diseases, especially cancer, with approximately 475,000 study participants. The German contribution amounted to 53,000 study participants recruited between 1994 and 1998. The study instruments of the baseline examination included self-administered questionnaires for optical reading, PC-guided interviews, and physical examinations. These instruments covered different aspects of lifestyle, with a particular focus on diet. In addition, about 95% of the participants provided 30 ml of blood. The blood was stored in liquid nitrogen for further use, preferentially in nested case-control studies. All interviews and examinations were conducted by trained interviewers in examination centers established for this study in local health offices. Every 2 years, a follow-up questionnaire is mailed to the study participants. The follow-up questionnaires will be used as the major source of outcome information and to update exposure information. The self-reported diseases are verified by medical data. In the future, record linkage with local cancer registries will help to support the identification and collection of incident cancer cases. Only an outline of hypotheses was formulated at the very beginning of EPIC in 1992. In the future, each etiological study will be based on detailed research hypotheses according to the existing knowledge and identified research gaps. These studies will be conducted on cancer at the international level and on non-cancer diseases at the national or local level.
Gesehen am 11.02.2019